Boron isotope sensitivity to seawater pH change in a species of Neogoniolithon coralline red alga. (15th November 2017) - Donald, Hannah K.; Ries, Justin B.; Stewart, Joseph A.; Fowell, Sara E.; Foster, Gavin L.
Abstract: The increase in atmospheric carbon dioxide (CO2 ) observed since the industrial revolution has reduced surface ocean pH by ∼0.1 pH units, with further change in the oceanic system predicted in the coming decades. Calcareous organisms can be negatively affected by extreme changes in seawater pH (pHsw ) such as this due to the associated changes in the oceanic carbonate system. The boron isotopic composition (δ 11 B) of biogenic carbonates has been previously used to monitor pH at the calcification site (pHcf ) in scleractinian corals, providing mechanistic insights into coral biomineralisation and the impact of variable pHsw on this process. Motivated by these investigations, this study examines the δ 11 B of the high-Mg calcite skeleton of the coralline red alga Neogoniolithon sp. to constrain pHcf, and investigates how this taxon's pHcf is impacted by ocean acidification. δ 11 B was measured in multiple algal replicates ( n  = 4–5) cultured at four different p CO2 scenarios – averaging (±1σ) 409 (±6), 606 (±7), 903 (±12) and 2856 (±54) μatm, corresponding to average pHsw (±1σ) of 8.19 (±0.03), 8.05 (±0.06), 7.91 (±0.03) and 7.49 (±0.02) respectively. Results show that skeletal δ 11 B is elevated relative to the δ 11 B of seawater borate at all pHsw treatments by up to 18‰. Although substantial variability in δ 11 B exists between replicate samples cultured at a given pHsw (smallest range = 2.32‰ at pHsw 8.19, largest range = 6.08‰ at pHsw 7.91), strong correlations are identified between δ 11 B and pHsw ( R 2  = 0.72, p  < 0.0001, n  = 16) and between δ 11 B and B/Ca ( R 2  = 0.72, p  < 0.0001, n  = 16). Assuming that skeletal δ 11 B reflects pHcf as previously observed for scleractinian corals, the average pHcf across all experiments was 1.20 pH units (0.79 to 1.56) higher than pHsw, with the magnitude of this offset varying parabolically with decreasing pHsw, with a maximum difference between pHsw and pHcf at a pHsw of 7.91. Observed relationships between pHsw and calcification rate, and between pHsw and pHcf, suggest that coralline algae exhibit some resilience to moderate ocean acidification via increase of pHcf relative to pHsw in a similar manner to scleractinian corals. However, these results also indicate that pHcf cannot be sufficiently increased by algae exposed to a larger reduction in pHsw, adversely impacting calcification rates of coralline red algae.